A Sociolinguistic Analysis of Addressee Terms Found in Babad Banjoemas Wirjaatmadjan - Chusni Hadiati; Rosdiana Puspita Sari; Usep Muttaqin (Lingua Cultura, 2022)
The research aimed to explain the addressee term found in Babad Banjoemas Wirjaatmadjan from a sociolinguistic point of view. This chronicle employed various kinds of addressee terms in Banyumas society. The method used is descriptive qualitative as it analyzed the variety of addressee terms and the social context of their use in a chronicle. The research results show five classifications of addressee terms found in Babad Banjoemas Wirjaatmadjan. They are (1) addressee terms that are related to the Dutch military, (2) addressee terms that are related to the position in the Indonesian government, (3) addressee terms that are related to descendants, (4) addressee term that is related to an object or thing, and (5) addressee term that is related to religion. These addressee terms are influenced by social factors such as the position in government (superior or inferior) and the aristocratic descendant.